Incorporating Computational Thinking into Education: From Teacher Training to Student Mastery - Nuzzaci, Antonella (Journal of Education and Training, 2024)
The concept of computational thinking originated in the 1950s and 1960s as “algorithmic thinking” (Denning, 2009), which involves using a systematic and precise sequence of steps to solve problems, potentially using computers to automate the process. Today, ’computational thinking’ is defined as is a solving problem process that involves formulating problems and solutions in a way that can be represented and solved through a series of computational steps, designing systems and understanding human behaviour, based on fundamental computer concepts. It includes processes such as abstraction and decomposition when dealing with complex tasks or designing extended systems (Wing, 2006). From an educational point of view, the challenge is to identify the cognitive skills that are expected of a person with this type of thinking and their ability to apply them in practice. Computational thinking encompasses a set of thought processes that originate from computer science, but are applicable in various fields. However, it is often wrongly perceived as “technological thinking”, which implies a mindset aimed exclusively at the effective use of technologies. The contribution points out that the lack of a clear definition hinders the integration of this concept into teacher training and broader educational contexts. If understood correctly, computational thinking could significantly improve understanding of the procedural aspects of knowledge, which are very useful for teaching. In this sense, the contribution also describes an exploratory research on the opinions of primary school teachers in central Italy aimed at understanding the perceived benefits that the incorporation of computational thinking could bring in a teaching context.